Understanding variation in the efficacy of financial participation across Europe: The role of country-level factors. (May 2018) - Williams, Mark
Little is known about variation in the efficacy of financial participation across countries. This article examines the relationship between two types of financial participation (profit-sharing and employee share-ownership) and labour productivity across 29 European countries using a representative workplace survey. Consistent with theoretical expectations, profit-sharing is associated with superior labour productivity when it is open to all employees, whilst the evidence for employee share-ownership is more mixed. Analysis reveals considerable variation in the efficacy of both schemes across Europe. Country-level collective bargaining coverage has the greatest explanatory power in accounting for cross-country variation in efficacy. In countries with higher levels of collective bargaining coverage, profit-sharing performs less well, whereas employee share-ownership performs better, relative to countries with lower collective bargaining coverage. These findings shed light on the comparative dimension of the financial participation–labour productivity link.